Sevoflurane addiction due to workplace exposure: A case report and literature review. Issue 38 (September 2018) - Luo, Ailin; Zhang, Xue; Li, Shiyong; Zhao, Yilin
Abstract: Rationale: Anesthesiologists have a well-known increased risk of substance abuse. High-concentration of inhalation anesthetics in exhaled air of operating room personnel is detected. such secondhand exposure produces neurobiological sensitization to the reinforcing effects of inhalation anesthetics. Patient concerns: An addictive young male anesthesiologist who was long-term abuse with sevoflurane after 4 years occupational exposure. A 28-year-old anesthesiologist on duty was found deeply sleep in the locker room and coved his nose with Gauze with high-concentration of sevoflurane. He was found addiction to sevoflurane second time. Several life-threatening incidents occurred including severe aspiration pneumonia. No other addiction was found in his history before he became severely dependent on sevoflurane. Diagnoses: A visual analog scale was employed to assess the severity of craving for sevoflurane and the Benzodiazepine Withdrawal Symptom Scale (BWSQ2)-scale was used to assess sevoflurane withdrawal syndrome(WS). Interventions: First time an opened original sevoflurane container filled with water instead of sevoflurane was handed out for a minute in order to elicit craving and withdrawal symptom in five therapeutic single-sessions. Second time an opened original sevoflurane container filled with sevoflurane instead of water was used as his powerful cur-stimulus and also was handed out for a minute. Outcomes: After professional therapy and continuous surveillance he was rehabilitation and back to work. However, after three weeks he became addiction to sevoflurane again. He showed very sensitive to sevoflurane and switched to other career. Lessons: This case emphasizes that secondhand exposure to inhalation anesthetics may be dangerous and increase the life-threatening professional risk to anesthesiologists, although identification of the responsible factor remains difficult. However, the safety of operating room staff should be aroused wide-spread social concern.